Special judo fitness test in juvenile junior and senior Brazialian judo players - Franchini, E.; Nakamura, F. Y.; Takito, M. Y.; Kiss, M. A.; Sterkowicz, S.
The present study objectified to verify if there was difference in the performance of a specific anaerobic lactic test of judo in athletes of different age groups (Juvenile, Junior and Senior) submitted to same training. The sample was constituted of 06 judoists of the Juvenile class, 05 judoists of the Junior class and 06 judoists of the Senior class, that agreed in participating of the research after informed consent. The test was accomplished as proposed by STERKOWICZ (1995) and the data were analyzed through an ANOVA one way followed by Tukey test when found significant difference. It was not found any difference among the groups in the performance of the test, indicating that athletes with superior age to 16 years submitted to the same training type tend to have similar performance in the test proposed by STERKOWICZ (1995).Those findings needs further research, yet.